Breed, age, and social environment are associated with personality traits in dogs - Salonen Milla; Mikkola Salla; Niskanen Julia E; Hakanen Emma; Sulkama Sini; Puurunen Jenni; Lohi Hannes (Elsevier, 2025)
Personality in pets and other domesticated animals is important for their well-being and it can also influence human-animal relationships. Genetic and environmental factors influencing unwanted behavior in dogs are somewhat well known, but the factors influencing dog personality remain understudied. Here we examined environmental and demographic factors associated with seven broad personality traits in a survey of over 11,000 dogs. We utilized linear models and extensive model validation to examine the factors that have the most significant influences on personality and calculated effect sizes to assess the importance of these variables. Breed and age had the strongest associations with dog personality traits. Some environmental factors, especially puppyhood socialization, were also associated with personality. All factors had small effect sizes, highlighting that a lot of variation in personality remains unexplained. Our results indicate that personality traits are complex and strikingly similar in dogs, humans, and other nonhuman animals.